KINERJA DAN DISPOSISI MATEMATIS SISWA MELALUI PENERAPAN MODEL PROJECT-BASED LEARNING - Rosnawati Rosnawati; Rahmah Johar; Zainal Abidin (Universitas Syiah Kuala, 2019)
Performance requires students to be active in working on assignments, as the evaluation is not only on the products but the skills they have. Mathematical disposition of students is vital to consider. Lack of students’ participation in the learning process can lead to low students’ performance and mathematical dispositions. The Project-Based Learning (PjBL) model encourages students productive. They will work on a project whose learning activities are more interesting and tangible so that students can develop their mathematical performance and disposition. This study aimed to analyze the development of student performance in completing group and individual assignments and their mathematical disposition through the application of the PjBL model. This research applied a qualitative study describing the development of student performance and mathematical disposition. The research subjects were 30 Year 7 students from one class of SMP Negeri 3 Unggul Ingin Jaya Aceh Besar. Data collection techniques involved observation, interview and questionnaire. The research results showed that 1) students developed their performance in completing group assignments by conducting all stages of task completion; 2) students developed their performance in completing individual tasks by performing all stages of task completion; 3) the mathematical disposition of students after the learning with the PjBL model had improved, especially on indicators of interest and curiosity.